Penerapan Strategi Pembelajaran Kooperatif Tipe Problem Based Learning (PBL) untuk Meningkatkan Hasil Belajar Matematika Kelas VII C SMP Negeri 1 Koto Baru pada Materi Garis dan Sudut - Widiastuti Widiastuti (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This research is motivated by giving assignments or training, only some children want to find answers to questions that are considered difficult for them. Students who do not want to try or are lazy to find answers, just answer carelessly so that student learning outcomes are still low. This study aims to determine the increase in student mathematics learning outcomes through cooperative learning strategies type Problem Based Learning (PBL) kelas VII C SMP Negeri 1 Koto Baru in the form of Lines and Angles. This research is a Classroom Action Research. The research data is in the form of information about the process and data on the results of the action obtained from observations and tests. Research subjects were teachers, researchers and students of class VII C, totaling 30 people.Students' mathematics learning outcomes using the Problem Based Learning (PBL) cooperative learning strategy in cycles I and II have increased, where the average value in the first cycle is 66.33 and the second cycle is 89.00. Thus it can be concluded that learning mathematics using the cooperative learning strategy type Problem Based Learning (PBL) can improve the mathematics learning outcomes of class VII C students of SMP Negeri 1 Koto Baru.